Nereididae (Polychaeta) da costa nordeste do Brasil: III. Gêneros Ceratonereis e Nereis - Santos,Cinthya S. G. (2003)
Ten species belonging to the genera Ceratonereis Kinberg, 1866 and Nereis Linnaeus, 1758 were recorded in estuaries, exposed sandy beaches, shelly soft bottoms, atolls and coral reefs of the Brazilian northeastern coast. Two new species, Nereis serrata, from Ceará coast, and Nereis pseudomoniliformis, from Sergipe coast, are described.